Banalitas Salib dalam Khotbah Modern: Analisis Teologis dan Pastoral - Simanjuntak, Markus Adelbert (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2025)
The cross, as the core of Christian theology, undergoes banalization in modern Indonesian sermons, reduced to an emotional rhetorical tool, a guarantee of prosperity, or an individualistic solution, thus losing its eschatological, cosmic, and communitarian dimensions. This qualitative-descriptive study analyzes 37 digital sermon transcripts (2018–2024) from urban churches in Indonesia, employing Paul Ricoeur’s hermeneutics and biblical theology. Findings identify three patterns of banalization: emotionalistic, individualistic, and prosperity-therapeutic, which result in a crisis of church identity, stagnation in discipleship, and prophetic failure. Recovery strategies are proposed through expository-redemptive homiletics, participatory liturgy, and social contextualization, restoring the cross as a transformative force for individuals, the church, and society. This study offers theological and pastoral contributions to revitalizing the meaning of the cross in the context of Indonesian homiletics. AbstrakSalib, sebagai inti teologi Kristen, mengalami banalitas dalam khotbah modern di Indonesia, direduksi menjadi alat retorika emosional, jaminan kemakmuran, atau solusi individualistik, sehingga kehilangan dimensi eskatologis, kosmis, dan komunitarian. Penelitian kualitatif-deskriptif ini menganalisis 37 transkrip khotbah digital (2018–2024) dari gereja urban di Indonesia, menggunakan pendekatan hermeneutika Paul Ricoeur dan teologi biblika. Temuan mengidentifikasi tiga pola banalitas: emosionalistik, individualistik, dan prosperitas-terapeutik, yang berdampak pada krisis identitas gereja, stagnasi pemuridan, dan kegagalan profetis. Strategi pemulihan diusulkan melalui homiletika ekspositori-redemptif, liturgi partisipatif, dan kontekstualisasi sosial, yang mengembalikan salib sebagai kekuatan transformasi individu, gereja, dan masyarakat. Penelitian ini menawarkan kontribusi teologis dan pastoral untuk revitalisasi makna salib dalam konteks homiletika Indonesia.